Comparison Of ALT In Type 2 Diabetics with And Without Fatty Liver Disease - Kausar Malik; Faiza Batool; Lubna Meraj; Shazia Saddiq; Abrar Akbar; Hina Hanif Mughal (Journal of Rawalpindi Medical College)
Objective: To determine the association of alanine aminotransferase in type 2 diabetic patients with and without fatty liver disease.